Observation of up-conversion luminescence polarization control in Sm3+-doped glass under an intermediate femtosecond laser field. Issue 22 (28th February 2017) - Zheng, Ye; Cheng, Wenjing; Yao, Yunhua; Xu, Cheng; Feng, Donghai; Jia, Tianqing; Qiu, Jianrong; Sun, Zhenrong; Zhang, Shian
Abstract : The polarization modulation strategy of the femtosecond laser field was shown to be a well-established method to control up-conversion luminescence in rare-earth ions. Abstract : The polarization modulation strategy of the femtosecond laser field was shown to be a well-established method to control up-conversion luminescence in rare-earth ions. In this work, we further extend the polarization control behavior from weak to intermediate femtosecond laser fields. We experimentally show that the polarization control efficiency of the up-conversion luminescence in the Sm 3+ -doped glass will be affected by the femtosecond laser intensity, which decreases with the increase of the laser intensity. We theoretically propose a fourth-order perturbation theory to explain the experimental observation, which includes the two-photon and four-photon absorptions, and the destructive interference between the two-photon and four-photon absorption will result in the suppression of the polarization control efficiency due to their different polarization control degrees. These experimental and theoretical results provide a new insight into understanding the polarization control process of up-conversion luminescence in rare-earth ion doped luminescent materials under an intermediate femtosecond laser field, and also can open a new opportunity for the polarization control application in some related areas.